2021
DOI: 10.1590/1980-5373-mr-2020-0381
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Effect of Heat Treatment on the Compression Behavior of Aluminum Matrix Syntactic Foam Fabricated by Sandwich Infiltration Casting

Abstract: In this research, syntactic foams including Al-7075 matrix and 2-4 mm low-cost pumice particles were manufactured via a novel casting method called as sandwich infiltration. According to physical evaluations, thanks to extremely porous structure of pumice, density values of the fabricated foams varied between 1.42 and 1.61 g/cm 3. Porosity values were between 40.62% and 47.39%. Microstructural observations showed that there was a perfect infiltration between Al matrix and pumice particles because of correct pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…SFs produced by metallic matrices are known as metal matrix syntactic foams (MMSFs). MMSFs exhibit higher density than conventional metal foams (MFs) and demonstrate superior mechanical properties [9]. Based on the same concepts, a specific type of MMSF Processes 2022, 10, 478 2 of 24 can be found in the literature, referred to as composite metal foams (CMF).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SFs produced by metallic matrices are known as metal matrix syntactic foams (MMSFs). MMSFs exhibit higher density than conventional metal foams (MFs) and demonstrate superior mechanical properties [9]. Based on the same concepts, a specific type of MMSF Processes 2022, 10, 478 2 of 24 can be found in the literature, referred to as composite metal foams (CMF).…”
Section: Introductionmentioning
confidence: 99%
“…Major target sectors for implementing MMSFs include the automotive, railway, aerospace, and construction industries, due to the critical parameters that limit for the ability of designing new components: ductility, energy absorption, and low density. In transport industries (by ground, air, and water), lightweight components may enhance fuel efficiency and thus reduce pollutant emission [9]. Moreover, the superior reduction of dynamic loading properties makes them suitable for military vehicles and mine blast protection [3,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the previous papers are scrutinized, Taherishargh et al 22 found that 2.8-4 mm pumice-filled foams had a density range of 1.48-1.50 g/cm 3 . In another work, Bolat et al 21 produced 2-4 mm pumice-added AA7075 foams and the density levels exceeded 1.60 g/cm 3 . As for expanded glass, Bolat et al 15 applied the same technique offered in this paper and proclaimed that density intervals altered between 1.22-1.30 g/cm 3 and 1.41-1.50 g/cm 3 for 2-4 mm and 1-2 mm glass-filled samples, respectively.…”
Section: Physical Properties Of Hybrid Samplesmentioning
confidence: 96%
“…Also, it should be noted that compared to other reinforcement ceramics, pumice has a big potential and was studied solely in a few MMSF projects. [21][22][23] Figure 1 illustrates macro-and micro-images of the reinforcement particles. Furthermore, it is also true to say that although pumice and expanded glass particles display low elongation and poor ductility owing to their low fracture toughness, these ceramic materials provide a noteworthy rigidity and porosity to the aluminum matrix.…”
Section: Matrix and Reinforcement Ceramicsmentioning
confidence: 99%